Reproduction of intra-radicular surface anatomy of extracted human teeth: comparison of three different materials using injection technique (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):181-4.The abstract of this article is available on the PubMed website